2009
DOI: 10.1590/s1516-89132009000400023
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical quality changes in mangaba (hancornia speciosa gomes) fruit stored at different temperatures

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 5 publications
0
12
0
2
Order By: Relevance
“…Some early investigators reported that ascorbic acid content increased in the immediate postharvest period and then gradually declined. For example, Carnelossi et al (2009) reported an increase in vitamin C content in mangaba fruits after 2 days of storage at 24°C, followed by a sharp fall.…”
Section: Resultsmentioning
confidence: 99%
“…Some early investigators reported that ascorbic acid content increased in the immediate postharvest period and then gradually declined. For example, Carnelossi et al (2009) reported an increase in vitamin C content in mangaba fruits after 2 days of storage at 24°C, followed by a sharp fall.…”
Section: Resultsmentioning
confidence: 99%
“…modificações fisíco-químicas nos frutos da mangabeira após colheita, buscando compreender quais as variações encontradas em diferentes temperaturas de armazenamento (Carnelossi et al 2004;Carnelossi et al 2009), e em diferentes temperaturas de armazenamento com atmosfera modificada por filme (Soares Junior et al 2008;Santos et al 2009;Campos et al 2011). …”
Section: Os Cinco Trabalhos Enquadrados Nas áReas Fisiologia Pós-colhunclassified
“…Lee and Kader (2000) reported that, although the ascorbic acid content decreases with maturation, there may be an increasing trend due to the increase in the total volume of juice with advancing maturation process. This increase can be analyzed at the twentieth day of storage, but it is also the result of oxidative reactions that vitamin C undergoes during ripening by acting as a molecule with antioxidant properties (Carnelossi et al, 2009). Ascorbic acid has characteristics of unstable molecule that may undergo auto-oxidation into dehydroascorbic acid, which although being reversible, may cause losses in product quality (Gonçalves and Maia Campos, 2009) and lead to increased and decreased contents in stored fruits.…”
Section: Ascorbic Acid Contentmentioning
confidence: 99%